PENGUATAN EKONOMI USAHA MIKRO DAN KECIL MELALUI SERTIFIKAT HALAL “SELF DECLARE” - Tuti' Nadhifah; Nunung Agus Firmansyah; Ahmad Nur Syafiq; Nurul Islamiyah; Alif Kiky Listiyati (Jurnal Abdimas Indonesia, 2023)
PPH or what can be called Halal Product Process Assistance in PDM Kudus is a community service activity where this service assists micro and small business actors in PDM Kudus City in order to assist in making or processing the halal products or services they have. The Free Halal Certification Program (SEHATI) is a program planned by the government and is free of charge, meaning it is free. This program is offered by the Ministry of Religion through BPJPH or commonly referred to as the body that administers halal product guarantees. The SEHATI program was initiated with the aim of being a strategy to accelerate the increase in the number of micro and small business actors to become halal certified. This service activity uses the PAR (Participatory Action Research) method. The PAR method was chosen because this service activity involves community participation, especially PDM members, in assisting activities regarding the halal product process in Kudus City. The business actors who are accompanied are business actors who become and take part in PDM (Regional Muhammadiyah Leadership) lectures with various kinds of food products. Mentoring activities apart from training micro and macro business actors, also assist micro and small business actors in filling out the SJPH Manual and filling in business actor statements via the SiHalal application. Apart from that, this assistance also helps small and micro business actors in PDM in inputting data into the SiHalal application, after which verification and validation are carried out on products or services registered in the SiHalal application in the SEHATI program. Based on this, the result of this service activity is obtaining halal certification for products or services by micro and small business actors in PDM Kudus City. This mentoring activity serves to obtain more added value and further guarantee a product or service that they are proposing to obtain a halal certificate through the SEHATI (Free Halal Certificate) program. Apart from that, the result of this service activity is to provide an explanation of the importance of halal certification. Apart from being able to guarantee the halalness of products, it can also be an economic booster such as increasing market share and increasing business competitiveness. Products will be more accepted in the market, especially among Muslim consumers who need halal products in both domestic and international markets.